The Effect of Finger Painting Media Implementation on Audio Fine Motor Skills - Pascalian Hadi Pradana (Pusat Penerbitan Universitas (P2U) Unisba, 2019)
This research aims to determine the effect of the application of Finger Painting Learning Media on the development of fine motor skills in early childhood. The design carried out by researchers in this research uses a quantitative approach to the type of Pre-Experiment, using an impure experimental model (one-shot case study) as an experiment is carried out there is no comparison of groups and also without preliminary tests. For the study of this research data, the independent variable (variable x) is the application of the Finger Painting media, and the dependent variable (variable y) is fine motor skills. The analysis used is Chi-Square, with a significance level of 1%, obtained then Xtable = 3,841 Xcount value = 6,12. Thus the value of Xcount> Xtable (6.12> 3.841) means, rejecting the null hypothesis (H0) and the working hypothesis (Ha) is accepted. Thus, There Is The Effect Of The Application Of Finger Painting Learning Media On The Improvement Of Fine Motor Ability In Early Childhood.Keywords: Fine Motorbike; Finger Painting. AbstrakRiset ini bertujuan agar melihat adanya Pengaruh Penerapan Media Pembelajaran Finger Painting Terhadap Pengembangan Kemampuan Motorik Halus Anak usia dini. Rancangan yang dilakukan penulis dalam riset ini memakai pendekatan kuantitatif dengan tipe Pre-Experiment, dengan menggunakan model eksperimen tidak murni (one-shot case study) sebagaimana suatu eksprimen dilakukan tidak ada pebandingan kelompok dan tidak ada pree test. Untuk Pengkajian data riset ini, yang menjadi variabel x (variabel bebasnya) yaitu penerapan media Finger Painting, beserta variabel y (variabel terikatnya) yaitu kemampuan motorik halus. Analisis yang digunakan yaitu Chi Kuadrat, dengan taraf signifikan 1%, didapat maka Xtabel = 3,841 nilai Xhitung = 6,12. Dengan demikian nilai Xhitung > Xtabel (6,12 > 3,841) berarti, menolak hipotesis nihil (H0) beserta hipotesis kerja (Ha) diterima. Sehingga, Ada Pengaruh Penerapan Media Pembelajaran Finger Painting Terhadap Peningkatan Kemampuan Motorik Halus Anak Usia Dini.Kata Kunci: Motorik Halus; Finger Painting.